PENGEMBANGAN MODEL PEMBELAJARAN SEPAK BOLA MELALUI PERMAINAN SEPAKBOLA GAWANG MULTI LEVEL BAGI SISWA KELAS V SD N SIWALAN KECAMATAN GAYAMSARI KOTA SEMARANG TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to produce a Learning Model Football Development Through Football Games Wicket Multi Level For Student Class V SD Negeri Semarang siwalan Sub Gayamsari Year 2013/2014 . The results showed that students' learning outcomes above completeness MOH set that is 75 experienced an increase that is on a small scale pilot study achieved 87.5 % completeness when in large scale trials completeness learn to reach 92.5 %. From the above data it can be concluded that it is seen from the results of field trial to be classified very good football learning model through multi level football game goal can be used in SD Negeri Semarang Gayamsari siwalan District . Recommendation : Based on the above findings , the physical education teacher at the School of State Policy siwalan free to use football learning model through multi level football game goal as a result of the expansion of the game model.